Pengembangan Media Pembelajaran IPA Interaktif Berbasis Keterampilan Proses Sains untuk Kelas Atas Sekolah Dasar - Riwanto, Mawan Akhir; rahayuni, Galuh (Jurnal Pancar, 2018)
The objectives of this research are (1) to develop interactive science learning media based on science process skills, and (2) to develop guidelines for developing interactive science learning media based on science process skills. This research is a research and development research. This research used the Borg & Gall research model. Borg & Gall (1989: 789-795) which consists of 10 stages. The research subjects involved in this research included elementary school teachers and students, media experts, and material experts. The results of this research are 1) interactive science learning media based on science process skills for grade 4 with 2013 curriculum contains 9 themes, while practicing science process skills that exist in students; 2) Quality of learning media based on science process skills, material experts, teachers, and students in the good category